"Connection With the Creator So Our Spirits Can Stay Alive": A Community-Based Participatory Study With the Métis Nation of Alberta (MNA)—Region 3. (December 2022) - Ginn, Carla S.; Ginn, Craig W. C.; Barnabe, Cheryl; Gervais, Lawrence; Gentes, Judy; Dumont/Vaness Bergum, Doreen; Rees, Noelle; Camponi, Ashley
In this article, we describe our Métis-guided community-based participatory research exploring health protective factors for mental health and addiction within the Métis Nation of Alberta (MNA)—Region 3. There is much research regarding the detrimental effects of colonialism but a lack of Métis-guided research contributing to understanding of individual, family, and community well-being. The primary aim of our study was to explore health protective factors for mental health and addiction challenges. Our study was informed by Indigenous ways of knowing, focusing on the connectedness of all things, and participatory action research, a philosophy and method focused on inclusion and community incorporation of local knowledge. Participants described the need to foster respect, trust, courage, wisdom, humility, truth, humor, esteem, honesty, acceptance, identity, and love, emphasizing well-being through connection with Creator. All authors but the first are members of the MNA—Region 3.